Vero cell culture on magnesium doped biphasic calcium phosphate scaffolds - Abd Rahim, Toibah; Sopyan, Iis; Mel , Maizirwan (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
The bioactivity test on the performance of porous microcarriers of pure biphasic calcium phosphate (BCP) and Mg-doped BCP was conducted in spinner vessel with Vero cell lines for 90 hours. The findings revealed that all the porous microcarriers were biocompatible as the cells already attached on the microcarrier after 24 hours of culture. The presence of divalent cations including Mg2+ is encouraged the spreading and adhesivity of cells onto bioceramic matrices. Magnesium also believed to increase the solubility of BCP in vitro which is useful to establish cell-material interface and thus improved cell attachment and growth. Thus, higher cell attachment, growth, and migration of cell deep inside the pores were obtained on microcarriers of 10 mol% Mg-doped BCP compared to undoped BCP. The substitution of Mg into the BCP present several advantages related to metabolic cell behaviours as FESEM results showed that Mg substitution can induce a spread-like and irregular morphology which is quite different from the cell grown onto the pure BCP where the cells just remain on the surface of the scaffold, or in a localized area within the scaffold and proliferate there. This makes porous Mg-doped BCP substrate a promising candidate as a bone substitute and microcarrier.